POLA PEWARISAN SIFAT DAN IMPLIKASINYA PADA TANAMAN CABAI (Capsicum sp.) : SYSTEMATIC LITERATUR REVIEW - Mia As Tutik (Program Studi Biologi Fakultas Sains dan Teknologi Universitas Islam Negeri Sumatera Utara, 2025)
ABSTRACTThis study aims to summarize research findings on the genetic inheritance patterns of chili pepper (Capsicum sp.) through a Systematic Literature Review (SLR). The need for this study arises from the limited integration between phenotypic and molecular analyses in Indonesian research, although both approaches are essential for supporting effective breeding programs. The review followed the PRISMA 2020 guidelines and used Publish or Perish to search relevant articles in Google Scholar published between 2015-2025. A total of 136 articles were identified, and after screening for duplication, relevance, and quality, 12 studies were selected for analysis. The results show that qualitative traits in chili peppers, such as fruit color and morphological characteristics, are generally controlled by one or two major genes and follow Mendelian patterns. Meanwhile, quantitative traits such as fruit weight, yield, and size tend to be polygenic with moderate to high heritability values. Molecular approaches, such as the use of SSR markers, have also been applied to identify traits related to disease resistance. These findings highlight the importance of combining phenotypic and molecular data to optimize selection strategies and support the development of superior chili varieties in tropical environments.Keywords: Breeding, Capsicum Sp., Genetics, Heritability, Inheritance